Synthesis and Antimycobacterial Activity of Thiazole Derivatives - Shiradkar, Mahendra; Bhandari, S.V.; Kale, Rajesh; Laghate, Animesh (Asian Journal of Chemistry, 2010)
In this paper, a series of thiazole derivative compounds were synthesized and their antimicrobial as well as antimycrobacterial activities are discussed. Many of these compounds have shown better antimicrobial and antimycrobacterial activities while others were inactive.